ANALISIS PROFITABILITAS DAN BREAK EVEN POINTUSAHA PETERNAKAN AYAM BROILER MILIK “DAMIN FARM” DI DESA PERBALAN KECAMATAN GUNUNGPATI SEMARANG - L. B. N Gultom,; S i. Santoso; E. Suprijatna (Universitas Wahid Hasyim, 2018)
The research intends to know the profitability and Break Even Point implemented in the Perbalan Village, Gunungpati, Semarang. Research obtained by Damin Farm with cattle scale ≥ 12000 chickensin Perbalan Village, Gunungpati, Semarang. The method used in this research is survey method. The study took place from June to August 2016. Data collection consisted of primary and secondary data. The data used in the research is direct interview and observation. Primary data were obtained through direct interviews with respondent owners and labor farms based on the questionnaire. The results showed that the calculation of total variable costs with the scale of the amount of broiler chicken maintenance as much as 10.000 – 13.000 1st periode to 10th period is Rp. 2.996.584.152 and total production cost from 1st periode to 10th period is Rp 3.119.435.929 and the average profitability obtained at Damin Farm broiler farm is as much as 6,84%, while the average of BEP is 2749,068 kg.Keywords: Number of chickens, variable cost, production cost, profitability and Break Even Point